2020
DOI: 10.3390/nu12071908
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa Polyphenols and Gut Microbiota Interplay: Bioavailability, Prebiotic Effect, and Impact on Human Health

Abstract: Cocoa and its products are rich sources of polyphenols such as flavanols. These compounds exert antioxidant and anti-inflammatory activities, accountable for cocoa health-promoting effects. However, cocoa polyphenols are poorly absorbed in the intestine, and most of them cannot reach the systemic circulation in their natural forms. Instead, their secondary bioactive metabolites are bioavailable, enter the circulation, reach the target organs, and exhibit their activities. In fact, once reaching the intestine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 79 publications
4
88
0
3
Order By: Relevance
“…B vitamins, magnesium, and fatty acids easily reach the brain through specific carriers exerting beneficial neuronal effects [ 26 , 28 ]. Moreover, as for other phytoderivates [ 29 , 30 ], spirulina phytocomplex can also affect the brain through a first interaction with the intestinal microbiota. In fact, preliminary in vivo evidence currently shows a bidirectional interaction between spirulina and the gut microbiota.…”
Section: Spirulina Microalgae: Sources Chemical Composition and Bioavailabilitymentioning
confidence: 99%
“…B vitamins, magnesium, and fatty acids easily reach the brain through specific carriers exerting beneficial neuronal effects [ 26 , 28 ]. Moreover, as for other phytoderivates [ 29 , 30 ], spirulina phytocomplex can also affect the brain through a first interaction with the intestinal microbiota. In fact, preliminary in vivo evidence currently shows a bidirectional interaction between spirulina and the gut microbiota.…”
Section: Spirulina Microalgae: Sources Chemical Composition and Bioavailabilitymentioning
confidence: 99%
“…The mechanisms that have been proposed to explain these biological actions of flavanols on the metabolic diseases are based on their capacity to act as antioxidants and to interact with numerous signaling pathways and DNA [ 11 , 13 , 14 , 62 , 65 ], although these molecular mechanisms remain to be fully elucidated. Lately, the binomial relationship between flavanols and microbiota and its impact on health and disease has also started to be considered [ 64 , 66 ]. Noteworthy, the impact of these natural compounds on metabolic diseases in terms of microbiota and immune system remains still largely unknown.…”
Section: Dietary Flavanolsmentioning
confidence: 99%
“…In addition, the intake of flavanol-rich foods can also modulate the diversity and composition of GM in vivo. It has been shown that flavanol consumption can increase beneficial gut bacteria, such as Lactobacillus and Bifidobacterium, whereas reduce the number of pathogenic ones, such as Clostridium perfringens [ 66 ]. More importantly, cocoa supplementation (the most flavanol-rich food) in rats during 6 weeks was able to modify the microbiota composition and positively modulated the intestinal immune system, through changes in the colonic TLR pattern [ 97 ].…”
Section: Interplay Of Dietary Flavanols and Gut Microbiota In Metamentioning
confidence: 99%
“…A recent systematic review has concluded that cocoa consumption plays an important role in the human metabolic pathway through reducing oxidative stress, which is widely known to play a key role in in pathogenesis of chronic diseases such as diabetes, cancer and cardiovascular disease 79 . Other recent studies have observed the effects of cocoa on the intestinal microbiota composition, which in turn have been linked to an improved glucose homeostasis and gut health 80–82 . Most publications linked those cocoa benefits to phenolic acids, and particularly flavanol composition, compounds that have been found to be dependent on cocoa origin 83 .…”
Section: Nutraceutical Properties and Human Healthmentioning
confidence: 99%
“…However, quality control techniques continue to aim towards more efficient and appropriate methodologies for the traceability of cocoa signatures. Chemometric methods have been implemented for characterizing key compositional markers such as volatiles, 12,100–103 fatty acids, 104 peptides, 11,67,105 bioactive compounds 82,106,107 and methylxanthines, 58,60 as well as heavy metals 56,108–111 and other contaminants 112,113 . From this perspective, a recent review on the traceability of cocoa origin has summarized and discussed destructive and nondestructive technologies providing examples aiming at assessing cocoa quality, the study of new functional properties, the detection of trace contaminants and the detection of authenticity 10 …”
Section: Authentication and Geographical Differentiation Of Qualitymentioning
confidence: 99%